2021
DOI: 10.1088/1361-6528/ac13ea
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale mechanical and electrical characterization of the interphase in polyimide/silicon nitride nanocomposites

Abstract: Polymer nanocomposites (pNC) have attracted wide interests in electrical insulation applications. Compared to neat matrices or microcomposites, pNC provide significant improvements in combined electrical, mechanical and thermal properties. In the understanding of the reasons behind these improvements, a major role was attributed to the interphase, the interaction zone between the nanoparticles (NP) and the matrix. Because of their nanoscale dimensions, the interphase properties are mostly theoretically describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The interface is presumed with a width of tens of nanometers. To explain the excellent performance of PNDs, the interface has been considered to be of unique features such as modified permittivity and local states for charge trapping. , In recent years, with the use of EFM, these hypotheses can be checked directly by experiments. , For example, Sharma et al used EFM to investigate the charge density and permittivity in the interface . With a time-resolved EFM, Chen et al revealed that the interface near the PS–COOH nanoparticles exhibits greater polarization than that near the PS nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interface is presumed with a width of tens of nanometers. To explain the excellent performance of PNDs, the interface has been considered to be of unique features such as modified permittivity and local states for charge trapping. , In recent years, with the use of EFM, these hypotheses can be checked directly by experiments. , For example, Sharma et al used EFM to investigate the charge density and permittivity in the interface . With a time-resolved EFM, Chen et al revealed that the interface near the PS–COOH nanoparticles exhibits greater polarization than that near the PS nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The EFM seems to provide a promising approach to learning the interface in PNDs, but divergence in interpreting the EFM results arises and draws our attention. Namely, the influence from morphology is inadequately discussed ,, or even ignored ,,,,, in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the interphase width of 82 nm, the phase shift parameter of −0.08 ± 0.01 °/V² measured over the BN nanoparticle and its interphase leads to a relative dielectric permittivity of the interphase of 1.4 ± 0.2. An interphase area with a lower dielectric permittivity than matrix one has already been observed for various nanocomposites, particularly for polyethylene based one, such as PE/TiO2 [11], PE/Al2O3 [12], or polyimide/Si3N4 [10]. Results published in [11] on PE/TiO2 NC have shown practically the same value of the interphase permittivity (εri = 1.6).…”
Section: B Interphase Thickness Measurement By Pf-qnmmentioning
confidence: 64%
“…Secondly, a major role was attributed to the interphase and the interaction zone between the NBT nanowires and the PVDF matrix. For ferroelectric nanocomposite, the interphase of the dielectric permittivity is higher than that of the matrix because of the polarization enhancement in the interphase [ 4 , 50 , 51 , 52 ]. As the loading of NBT nanofibers increases, it is inevitable to introduce a small number of defects.…”
Section: Resultsmentioning
confidence: 99%